A Model of Religious Moderation Guidance by Islamic Religious Education Teachers Through the Rohis Extracurricular at SMA Negeri 1 Purwokerto - Muhammad Fakhriz Zaman; Mawi Khusni Albar (Aslim: Journal of Education and Islamic Studies, 2025)
This study aims to describe the role of Islamic Religious Education (PAI) and Character teachers in fostering students' religious moderation through Islamic Spirituality (Rohis) activities at SMA Negeri 1 Purwokerto. The background of this research is rooted in the urgency of strengthening the values of religious moderation among high school students, especially in the midst of rapid information flow and the emergence of extreme religious understandings that may influence students' perspectives. This research employed a descriptive qualitative method with data collected through observation, in-depth interviews, and documentation, and analyzed using Miles and Huberman's interactive model. The findings reveal that PAI and Character teachers act as educators, spiritual mentors, facilitators of activities, and role models (uswah hasanah) in internalizing moderation values, including tolerance (tasamuh), balance (tawazun), and fairness (i'tidal). The implementation of religious moderation is carried out through regular Islamic studies, worship habituation, social service activities, and Rohis programs involving collaboration with various student organizations. These activities effectively enhance students' moderate attitudes, reflected in their increased tolerance, openness, and harmonious interactions among peers of different religious backgrounds. This study highlights the strategic role of PAI teachers in shaping students' moderate, inclusive, and nationally oriented religious character.